Framework for Benchmarking green building movement: A case of Brazil. (July 2019) - Zhao, Dong; Miotto, Ana Beatriz; Syal, Matt; Chen, Jiayu
Highlights: A new sociotechnical angle to define and measure green building movement. New conceptual framework and KPIs for benchmarking green building movement. A case study in the context of Brazil using data available from English and Portuguese. A new paradigm indicates the sequence of GBM milestones. Implications for policymakers and city planners to promote green buildings. Abstract: Green building technologies and practices have been diffused globally along the progress of urban development and renewal. An increasing number of studies focus on the diffusion progress as a social movement. The concept of "green building movement (GBM)" has emerged in multiple disciplines for years; however, its definition remains ambiguous. This paper reports an approach to benchmarking GBM with a case study in the context of Brazil. The benchmarking approach includes a conceptual framework and four key performance indicators (KPIs) which are the institutional organization, professional organization, public policy, and public behavior. The case study results in best practices for Brazil to promote green buildings. The findings identify a GBM paradigm that indicates a pathway in the sequence of: formation of government agency; enactment of laws and regulations; introduction of new industry standards; emergence of incentive policies; and market adoption of green buildings. The findings highlight GBM as top-down progress and suggest a strong involvement from the political realm. The findings also underline big social events as a great opportunity to accelerate GBM. The implications produced from this study are applicable for policymakers in Brazil and other developing countries to adopt green buildings and facilitate a sustainable society.